2022
DOI: 10.34044/j.kjss.2022.43.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the factors influencing users’ satisfaction and continuance intention of MOOCs in China

Abstract: Recently, Massive Open Online Courses (MOOC) have received much attention from users. Users' continuance intention of using MOOC is one of the most important indicators to measure the success of MOOCs. At present, MOOCs are facing a low completion rate and retention rate problems. This calls for the importance in investigating factors that affect MOOC users' satisfaction, thereby enhancing the intention to continue using MOOCs. The purpose of this research was therefore to explore the factors affecting MOOC us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Such attempts were made by Suriazdin et al, (2022) who combined ECM with technology attractiveness and they discovered findings that were in line with those of ECM, with the exception of the perceived usefulness on continuing intention. Nong et al, (2022) combined ECM with perceived service quality in examining the MOOC continuance intention in China and the results corroborated the ECM findings and in addition found the significant influence of perceived service quality on satisfaction and continuation intention. In other contexts, Gupta et al, (2020) combined UTAUT (pre-adoption performance expectancy and effort expectancy) and post-adoption ECM (along with perceived usefulness and satisfaction, the other post-adoption factors are user interface quality, self-efficacy, security) in continuance intention to use M-wallets, Malik & Rao (2019) applied extended ECM in predicting the continuance intention of users of on-demand ride services.…”
Section: Expectation Confirmation Modelsupporting
confidence: 67%
See 1 more Smart Citation
“…Such attempts were made by Suriazdin et al, (2022) who combined ECM with technology attractiveness and they discovered findings that were in line with those of ECM, with the exception of the perceived usefulness on continuing intention. Nong et al, (2022) combined ECM with perceived service quality in examining the MOOC continuance intention in China and the results corroborated the ECM findings and in addition found the significant influence of perceived service quality on satisfaction and continuation intention. In other contexts, Gupta et al, (2020) combined UTAUT (pre-adoption performance expectancy and effort expectancy) and post-adoption ECM (along with perceived usefulness and satisfaction, the other post-adoption factors are user interface quality, self-efficacy, security) in continuance intention to use M-wallets, Malik & Rao (2019) applied extended ECM in predicting the continuance intention of users of on-demand ride services.…”
Section: Expectation Confirmation Modelsupporting
confidence: 67%
“…It states that the confirmation of past expectations will increase the user's perceived usefulness and vice versa. Since the ECM model has been thoroughly covered in the literature (Bhattacherjee, 2001a, b;Bhattacherjee & Premkumar, 2004;Dai et al, 2020;Ouyang et al, 2017;Yang et al, 2022;Rahmania et al, 2022;Suriazdin et al, 2022;Nong et al, 2022;Lee, 2010;Gupta et al, 2020;Malik & Rao, 2019;Jin et al, 2010), the current study just briefly summarises the theory. The conceptual model (Fig.…”
Section: Expectation Confirmation Theory (Ect) and Expectation Confir...mentioning
confidence: 99%
“…Extant studies confirmed the significant association among confirmation, satisfaction and usefulness of product (Ambalov, 2018;Gupta et al, 2020). Moreover, the relationship has been validated in varied contexts such as e-learning (Roca et al, 2006;Lee, 2010), Web portal (Lin et al, 2005), fitness and health apps (Chiu et al, 2020), mobile internet users (Jumaan et al, 2020) and massive online open course (MOOCs) (Nong et al, 2022). Based on these arguments, we hypothesize that:…”
Section: Confirmationmentioning
confidence: 77%
“…Furthermore, Bhattacherjee (2001) posited that a relationship between satisfaction and continuance is considered core in the context of information systems and the strongest in the context of electronic services (Liao et al, 2007), using blogs for learning and its continuing usage intentions (Ifinedo, 2018). Earlier studies confirmed the positive influence of satisfaction on information technology continuance usage (Bhattacherjee et al, 2008), in the context of brand extension products (Guo et al, 2018), mobile apps (Tam et al, 2020) and information technology (Steelman and Soror, 2017;Zhu et al, 2022;Nong et al, 2022). Therefore, we hypothesize that:…”
Section: Satisfactionmentioning
confidence: 86%
See 1 more Smart Citation